The Analysis of the Implementation of the Merdeka Curriculum Teaching Module Based on Problem-Based Learning in Physics Education at SMA Negeri 1 Kota Jambi - Rahma Dani; May Yani Br Sembiring; Anggrek Adewina Siahaan; Susantri Tarigan; Edo Markus Putra Harhar Ginting; Gheriyah Rohimah Nur Fatimah; Suwanto Suwanto (The Future of Education Journal, 2024)
This study analyzes the implementation of the Merdeka Curriculum using the Problem-Based Learning (PBL) model and its impact on student learning outcomes at SMA Negeri 1 Jambi. Using a qualitative approach, data were collected through direct observation and analysis of learning outcomes from class XII F7 students. The results indicate a significant increase in student engagement and learning outcomes through the PBL approach, with an average score improvement of 15% compared to conventional teaching. The PBL model successfully created a collaborative learning environment that encouraged problem-solving skills development. Despite initial challenges in teacher adaptation and resource availability, the implementation of the Merdeka Curriculum with the PBL model showed positive effects on student motivation and conceptual understanding. This study provides empirical evidence of the effectiveness of integrating PBL into the Merdeka Curriculum to enhance the quality of learning at the senior high school level.